Recent Publications (Quarterly Journal of Economics, 1951)
Recent Publications Get access The Quarterly Journal of Economics, Volume 65, Issue 1, February 1951, Page 148, https://doi.org/10.1093/qje/65.1.148 Published: 01 February 1951